Effects of Shuxuetong injection applied in acute ischemic stroke - Wei Zhang (Journal of Acute Disease, 2016)
Objective: To study the effects of Shuxuetong injection in adjuvant treatment of ischemic stroke on the degree of nerve injury, lipid metabolism and blood coagulation function. Methods: Patients with ischemic stroke admitted in our hospital during the period from May 2012 to May 2015 were selected for retrospective analysis. They were divided into the control group receiving regular treatment and the Shuxuetong group receiving adjuvant treatment with Shuxuetong injection. One and the three months after treatment, serum was collected and nerve injury molecules, indexes of lipid metabolism and blood coagulation function were measured. Results: One month after treatment, the contents of neuron-specific enolase, S100 calcium binding protein B, total cholesterol, triglyceride, low-density lipoprotein, oxidized low-density lipoprotein, thromboxane B2, fibrinogen and D-dimer in the serum of patients from Shuxuetong group were significantly lower than those of control group. The contents of high-density lipoprotein and 6-keto prostaglandin F1a were significantly higher than those of control group. Three months after treatment, the contents of neuron-specific enolase, S100 calcium binding protein B, total cholesterol, triglyceride, low-density lipoprotein, oxidized low-density lipoprotein, thromboxane B2, fibrinogen and D-dimer in the serum of patients from Shuxuetong group were significantly lower than those of control group. The contents of high-density lipoprotein and 6-keto prostaglandin F1a were significantly higher than those of control group. Conclusions: Adjuvant treatment with Shuxuetong injection can reduce the injury of nerve function of patients with ischemic stroke and improve blood lipid metabolism and blood coagulation function, which is an effective drug for the treatment of ischemic stroke.